Revisiting the dilemma between cohesion and openness. Issue 11 (2nd November 2018) - Callois, Jean-Marc
ABSTRACT: This paper revisits the old debate between export competitiveness and local economic cohesion. It builds a simple model of the trade-off between resource allocation inside or outside a region, which allows for the construction of a synthetic indicator of local economic interdependence. Openness is measured by the share of businesses belonging to an exporting sector. Next, it examines the relationship of these indicators with employment growth in metropolitan France. Both interdependence and openness influence employment growth positively, but their effects depend on both the macroeconomic and local context. These results bring new insights for a finer design of regional policies.